The methodology of project competence formation for the automatics of the normal modes for future grid automation engineers - Rudevich, N. (Problems of Engineer-Pedagogical Education, 2018)
An application of teaching method for forming of project competence on automatics of the normal modes for future grid automation engineers is devoted in the article. The educational planning is carried out for devices that would realize tasks of automatic control for parallel work, automatic voltage variation and reactive power, automatic frequency regulation and active power of synchronous generator. Planning is conducted in accordance with the basic stages of teaching method: acquaintance with the object of management; forming of knowledge, abilities, skills on determination of requirements, setting, principle of action and structure of making elements of control system; forming of knowledge, abilities, skills on determination of realization and parameters of making elements of control system; checking of the projected control system for compliance with requirements. General methodology of the project competence formation on automatics of the normal modes for future engineers on automation of grids on the base of causal model is defined.